We Can Better Manage Ecosystems by Connecting Solutions to Constraints: Learning from Wetland Plant Invasions - Adams, Carrie Reinhardt; Hovick, Stephen M.; Anderson, Neil O.; Kettenring, Karin M. (Frontiers in Environmental Science, 2021)
Wetlands provide critical wildlife habitat, improve water quality, and mitigate the impacts of floods, droughts, and climate change. Yet, they are drained, filled, dredged, and otherwise altered by humans, all of which contribute to their high susceptibility to plant invasions. Given the societal significance of wetlands and the disproportionately large amount of time and money spent controlling invaders in remaining wetlands, a fundamental shift must occur in how we approach restoration of plant-invaded wetlands. The need for more research is often used as an excuse for a lack of progress in invader management but, in fact, constraints to invader management are spread across the science, management, and stakeholder engagement domains. At their intersection are “implementation gap” constraints where the monumental efforts required to bridge the gap among scientists, managers, and community stakeholders are often unassigned, unrewarded, and underestimated. Here we synthesize and present a portfolio of broad structured approaches and specific actions that can be used to advance restoration of plant-invaded wetlands in a diversity of contexts immediately and over the long-term, linking these solutions to the constraints they best address. These solutions can be used by individual managers to chart a path forward when they are daunted by potentially needing to pivot from more familiar management actions to increase efficiency and efficacy in attaining restoration goals. In more complex collaborations with multiple actors, the shared vocabulary presented here for considering and selecting the most appropriate solution will be essential. Of course, every management context is unique (i.e., different constraints are at play) so we advocate that involved parties consider a range of potential solutions, rather than either assuming any single solution to be universally optimal or relying on a solution simply because it is familiar and feasible. Moving rapidly to optimally effective invasive plant management in wetlands may not be realistic, but making steady, incremental progress by implementing appropriate solutions based on clearly identified constraints will be critical to eventually attaining wetland restoration goals.